Antarctica Legislation, 1961 : hearings before the United States House Committee on Interior and Insular Affairs, Subcommittee on Territorial and Insular Affairs, Eighty-Seventh Congress, first session, on Aug. 24, 25, 1961. - United States. Congress. House. Committee on Interior and Insular Affairs. Subcommittee on Territorial and Insular Affairs. (Washington : U.S. G.P.O., 1962)
Considers (87) H.R. 7149, (87) H.R. 7475, (87) H.R. 7486, (87) H.R. 7489. Committee Serial No. 11. Considers H.R. 7149 and similar bills, to conduct, coordinate, and administer Antarctica research programs, and to establish the Richard E. Byrd Antarctic Commission. Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc. Indexed in CIS US Congressional Committee Hearings Index Part VII Considers (87) H.R. 7149, (87) H.R. 7475, (87) H.R. 7486, (87) H.R. 7489. Committee Serial No. 11. Considers H.R. 7149 and similar bills, to conduct, coordinate, and administer Antarctica research programs, and to establish the Richard E. Byrd Antarctic Commission. Mode of access: Internet.